Functional Features of National Thermal Power Plantsunder Sustainable Development Conditions - Kuznetsova, Mariya (Social Economics, 2019)
The paper is devoted to analysis of functional peculiarities of thermal power plants in Ukraine. In the course of the study, key determinants of the sustainable development of domestic electricity generation were identified in the context of transition to a new market model. The preconditions of activation and support of the sustainable development concept implementation process in the modern business practice of the energy sector enterprises within the Ukrainian economy are outlined.The theoretical and practical bases for ensuring the sustainable development of energy in relation to other United Nations Declarations of Sustainable Development are indicated. The comparative estimation of the efficiency level of state policy in scope of energy independence and resource conservation with the use of a complex indicator of GDP energy intensity is given. On the basis of international and domestic statistical data the dynamics of volumes of electricity production in Ukraine for the period of 1990-2017 as well as the structure of electricity generation by type of generation were analyzed. The dynamics of electric power generation in Ukraine by types of raw materials was presented in complex with the dynamics of coal consumption and production for the corresponding period. The peculiarities of thermal power plants functioning in comparison with other power generating enterprises in modern conditions are specified. The key element of Ukraine’s energy independence – the volume of proven coal reserves – is a prerequisite for the efficient functioning of domestic thermal power plants. The pricing features in the sphere of electricity production and sales are outlined, in particular, the structure of market rate and the price of electricity sales by producers to the Wholesale Market are presented. The significance of the innovation factor in the process of improving the efficiency of thermal power plants functioning has been substantiated, taking into account the economic, social and environmental aspects of their production and economic activity.